1997
DOI: 10.1016/s0008-6363(96)00213-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of angiotensin II-induced increase in aortic wall mass on compliance in rats in vivo

Abstract: An increase in aortic wall mass resulting from chronic infusion of angiotensin II does not alter the dynamic compliance of the vessel under isobaric conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…These results agree with the finding that arterial wall hypertrophy can be associated with opposing effects on the elastic properties of the carotid artery in patients. 13 Furthermore, previous studies showed that the increase in wall mass resulting from chronic Ang II infusion failed to alter compliance in rat aortas 14 and that differences in compliance between hypertensive and normotensive rat aortas having similar medial cross-sections could be attributed to differences in collagen cross-linking. 15 Here we identified MMP-9 as a key element in regulating vessel compliance, influencing type I and IV collagen accumulation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with the finding that arterial wall hypertrophy can be associated with opposing effects on the elastic properties of the carotid artery in patients. 13 Furthermore, previous studies showed that the increase in wall mass resulting from chronic Ang II infusion failed to alter compliance in rat aortas 14 and that differences in compliance between hypertensive and normotensive rat aortas having similar medial cross-sections could be attributed to differences in collagen cross-linking. 15 Here we identified MMP-9 as a key element in regulating vessel compliance, influencing type I and IV collagen accumulation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Dia is the arterial diameter (27). Replacing the elastic modulus by this relation, we can obtain the BramwellHill equation (Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Vessel distensibility was evaluated in rings of pulmonary artery and aorta (length 3 mm) as distensibility 5 DD/DP?D, where DD is the difference of diameter before and after 1 mm of stretching, DP is the difference in pressure at the same points and D is the final diameter of the ring [17,18]. Endothelial function was assessed as the change in wall tension in response to cumulative doses of adenosine diphosphate (ADP), as previously described [13].…”
Section: Vessel Distensibility and Endothelial Functionmentioning
confidence: 99%